Critical assessment of the pH of children's soap - Bruna Rafaela Mendes; Danielle Midori Shimabukuro; Marjorie Uber; Kerstin Taniguchi Abagge (Brazilian Society of Pediatrics, 2016)
Objective: To evaluate the pH value of children's antibacterial soaps and syndets used in children's baths and verify whether there is information regarding pH on the product label. Methods: Quantitative, cross‐sectional, analytical observational study that included ninety soap samples, both in bar and liquid presentations, as follows: 67 children's soap (group 1), 17 antibacterial soaps (group 2), and six syndets (group 3). Each sample had its pH measured after 1% dilution. In addition to descriptive statistics, the Pearson‐Yates chi‐squared test and Student's t‐tests were applied, considering the minimal significance level of 5%. The Wilcoxon‐Mann‐Whitney test, Fisher's exact test, and the Kruskal‐Wallis test were used for inferential statistics. Results: The pH levels varied considerably between liquid and bar presentations, with lower levels (4.4 to 7.9) found for the liquids (p < 0.05). Syndets showed pH levels close to the ideal (slightly acid) and the antibacterial soaps showed the highest pH levels (up to 11.34) (p < 0.05). Only two of the soaps included in the study had information about their pH levels on the product packaging. Conclusions: Knowledge of the pH of children's soap by doctors and users is important, considering the great pH variability found in this study. Moreover, liquid soaps, and especially syndets, are the most recommended for the sensitive skin of neonates and infants, in order to guarantee skin barrier efficacy.